Some Further Generalizations of Hölder's Inequality and Related Results on Fractal Space. (6th July 2014) - Chen, Guang-Sheng; Srivastava, H. M.; Wang, Pin; Wei, Wei
Abstract : We establish some new generalizations and refinements of the local fractional integral Hölder's inequality and some related results on fractal space. We also show that many existing inequalities related to the local fractional integral Hölder's inequality are special cases of the main inequalities which are presented here.